2016
DOI: 10.1111/jne.12349
|View full text |Cite
|
Sign up to set email alerts
|

Des‐Acyl Ghrelin Directly Targets the Arcuate Nucleus in a Ghrelin‐Receptor Independent Manner and Impairs the Orexigenic Effect of Ghrelin

Abstract: Ghrelin is a stomach-derived octanoylated peptide hormone that plays a variety of well-established biological roles acting via its specific receptor known as growth hormone secretagogue receptor (GHSR). In plasma, a des-octanoylated form of ghrelin, named des-acyl ghrelin (DAG), also exists. DAG is suggested to be a signalling molecule that has specific targets, including the brain, and regulates some physiological functions. However, no specific receptor for DAG has been reported until now, and, consequently,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(55 citation statements)
references
References 47 publications
3
47
0
5
Order By: Relevance
“…Ghrelin is also secreted as a des-octanoylated version, named des-acyl-ghrelin, which circulates in plasma at even higher levels than ghrelin because it is also produced in plasma by ghrelin deacylation [106]. Des-acyl-ghrelin fails to bind to GHSR-1a at physiological concentrations, and it may display some GHSR-1a-independent actions [107]. However, the role of des-acyl-ghrelin as a hormone is also uncertain since no specific receptor for this peptide has been reported, yet [7].…”
Section: Ghrelin Synthesismentioning
confidence: 99%
“…Ghrelin is also secreted as a des-octanoylated version, named des-acyl-ghrelin, which circulates in plasma at even higher levels than ghrelin because it is also produced in plasma by ghrelin deacylation [106]. Des-acyl-ghrelin fails to bind to GHSR-1a at physiological concentrations, and it may display some GHSR-1a-independent actions [107]. However, the role of des-acyl-ghrelin as a hormone is also uncertain since no specific receptor for this peptide has been reported, yet [7].…”
Section: Ghrelin Synthesismentioning
confidence: 99%
“…Nonetheless, des-acyl ghrelin exhibits several biological actions such as decreasing anxiety after intraperitoneral injection in receptor knockout mice (30). Peripheral or intracerebroventricular pretreatment with des-acyl ghrelin blunts the orexigenic action of ghrelin in rats (31) and mice (32). Des-acyl ghrelin's action takes place in a subset of arcuate nucleus neurons distinct from those activated by ghrelin (32).…”
Section: Modulation Of Gut-brain Signaling Under Conditions Of Stressmentioning
confidence: 99%
“…Peripheral or intracerebroventricular pretreatment with des-acyl ghrelin blunts the orexigenic action of ghrelin in rats (31) and mice (32). Des-acyl ghrelin's action takes place in a subset of arcuate nucleus neurons distinct from those activated by ghrelin (32). Studies using fluorescein des-acyl ghrelin injected intracerebroventricularly in mice demonstrate that the peptide binds selectively and mainly on arcuate neurons in a GHSR1a independent manner (32).…”
Section: Modulation Of Gut-brain Signaling Under Conditions Of Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…35 In line with this finding, a recent study showed that desacyl ghrelin antagonizes the orexigenic effect of peripherally administered ghrelin in mice. 36 This points towards a counteracting function of desacyl ghrelin to modulate/balance ghrelin's food intake-stimulating effect. This antagonism was also observed on colorectal motility: desacyl ghrelin reduced the motility-…”
Section: Introductionmentioning
confidence: 99%